A new species of Paranecepsia (Euphorbiaceae-Acalyphoideae) from Madagascar and its relationships among the ‘alchorneoids clade’ - Barberá, Patricia; Lachenaud, Olivier; Riina, Ricarda (European Journal of Taxonomy, 2022)
The formerly monotypic genus Paranecepsia Radcl.-Sm. is expanded with the description and illustration of a second species, Paranecepsia andrafiabensis Barberá & O.Lachenaud sp. nov. Molecular phylogenetic analyses of plastid rbcL and trnL-F data confirm a sister relationship between the new species and P. alchorneifolia Radcl.-Sm., as members of the alchorneoids clade. Paranecepsia andrafiabensis sp. nov. is notable for expanding the character states for the genus (now including both 2- and 3-locular ovary species) and broadening the geographic range of the genus from continental Africa to Madagascar. The new species adds to the diverse karst limestone endemics of northwestern Madagascar, where it has a very restricted distribution at the base of the western wall of the Ankarana tsingy. An amended generic description of Paranecepsia and a key to the species are also presented. Paranecepsia andrafiabensis sp. nov. is provisionally assessed as VU D1 based on the IUCN Red List criteria.